Comparing temperature data sources for use in species distribution models: From in‐situ logging to remote sensing. Issue 11 (22nd July 2019) - Lembrechts, Jonas J.; Lenoir, Jonathan; Roth, Nina; Hattab, Tarek; Milbau, Ann; Haider, Sylvia; Pellissier, Loïc; Pauchard, Aníbal; Ratier Backes, Amanda; Dimarco, Romina D.; Nuñez, Martin A.; Aalto, Juha; et al.
Abstract: Aim: Although species distribution models (SDMs) traditionally link species occurrences to free‐air temperature data at coarse spatio‐temporal resolution, the distribution of organisms might instead be driven by temperatures more proximal to their habitats. Several solutions are currently available, such as downscaled or interpolated coarse‐grained free‐air temperatures, satellite‐measured land surface temperatures (LST) or in‐situ‐measured soil temperatures. A comprehensive comparison of temperature data sources and their performance in SDMs is, however, currently lacking. Location: Northern Scandinavia. Time period: 1970–2017. Major taxa studied: Higher plants. Methods: We evaluated different sources of temperature data (WorldClim, CHELSA, MODIS, E‐OBS, topoclimate and soil temperature from miniature data loggers), differing in spatial resolution (from 1″ to 0.1°), measurement focus (free‐air, ground‐surface or soil temperature) and temporal extent (year‐long versus long‐term averages), and used them to fit SDMs for 50 plant species with different growth forms in a high‐latitudinal mountain region. Results: Differences between these temperature data sources originating from measurement focus and temporal extent overshadow the effects of temporal climatic differences and spatio‐temporal resolution, with elevational lapse rates ranging from −0.6°C per 100 m for long‐term free‐air temperature data to −0.2°C per 100 m for in‐situ soil temperatures. Most importantly, we found that the performance of the temperature data in SDMs depended on the growth forms of species. The use of in‐situ soil temperatures improved the explanatory power of our SDMs ( R 2 on average +16%), especially for forbs and graminoids ( R 2 +24 and +21% on average, respectively) compared with the other data sources. Main conclusions: We suggest that future studies using SDMs should use the temperature dataset that best reflects the ecology of the species, rather than automatically using coarse‐grained data from WorldClim or CHELSA.